Neutropenia Is an Underrecognized Finding in Pediatric Primary Immunodeficiency Diseases: An Analysis of the United States Immunodeficiency Network Registry. Issue 7 (October 2020) - Michniacki, Thomas F.; Connelly, James A.; Sturza, Julie; Merz, Lauren E.; Marsh, Rebecca; Dale, David; Garabedian, Elizabeth; Walkovich, Kelly
Abstract : Background: The frequency of neutropenia in pediatric primary immunodeficiency disorders (PIDDs) is unknown and potentially underappreciated. Our study aimed to determine the overall frequency and severity of neutropenia in children diagnosed with a PIDD entered in the United States Immunodeficiency Network (USIDNET) patient registry. Procedure: Neutropenia data and demographic/clinical information from 1145 patients younger than 21 years of age was obtained from the USIDNET registry. Results: Neutropenia is more common in PIDD patients entered within the USIDNET registry than previously appreciated. There was a >10% occurrence rate of neutropenia in all broad primary immunodeficiency categories as well as in nearly all individual PIDDs. Neutropenia frequency was greater in African American pediatric PIDD patients than in white or Asian patients. The degree of neutropenia did not associate with mortality in pediatric patients with a PIDD. Conclusion: Although our study did not assess the frequency of PIDD in patients presenting with neutropenia, the possibility of a primary immune disorder should be considered in patients with idiopathic neutropenia.